Determination of telaprevir in plasma of HCV‐infected patients by HPLC‐UV. Issue 9 (29th July 2013) - Tempestilli, Massimo; Milano, Elisa; D'Offizi, Gianpiero; Montalbano, Marzia; D'Avolio, Antonio; Gasperi, Tecla; Narciso, Pasquale; Ascenzi, Paolo; Pucillo, Leopoldo P.
Abstract Telaprevir is a direct acting antiviral agent, used with pegylated interferon and ribavirin for the management of chronic hepatitis C virus (HCV) genotype 1 infection, in patients not responding to therapy with pegylated interferon and ribavirin only. Although 75% of patients achieve a sustained virological response after treatment with telaprevir, adverse drug–drug interactions and undesirable events often occur. Therefore, telaprevir monitoring is pivotal to improve the management of HCV infection. Here, the first High‐Performance Liquid Chromatography‐Ultraviolet (HPLC‐UV) method to quantify telaprevir in human plasma of HCV‐genotype 1‐infected patients is reported. The volume of the plasma sample was 700 μL. This method involved automated solid‐phase extraction with Oasis HLB Cartridge 1 cc (divinylbenzene and N‐vinylpyrrolidone). The extracted samples were reconstituted with 150 μL of 60/40 water/acetonitrile. Thirty microliters of these samples was injected into a HPLC‐UV system, and the analytes were eluted on a X Terra® RP18 column (250 mm × 4.6 mm i.d.) with a particle size of 5 μm. The mobile phase (ammonium acetate buffer, 150 mM, pH 8.0, and methanol:acetonitrile 50:50) was delivered at 1.0 mL/min with linear gradient elution. The total run time for a single analysis was 16 min; telaprevir was detected by UV at 276 and 286 nm. The calibration curve was linear from 312.5 to 20, 000 ng/mL (r2 > 0.996). The absolute recovery of telaprevir ranged between 89 and 93% at concentrations of quality control samples of 800, 4, 000, 8, 000, and 16, 000 ng/mL. Both precision and accuracy were always <15%. The HPLC‐UV method reported here: (i) has been validated, (ii) is currently applied to monitor telaprevir in plasma of HCV‐infected patients, and (iii) appears useful in a routine laboratory. © 2013 IUBMB Life, 65(9):800–805, 2013